Correlation of Routinely Given Yoga Exercise With Level of Anxiety in Elderly of Yuswo Widodo Integrated Service Post Surabaya - Margareth, Felicia; Waworuntu, Gladdy S; Maramis, Willy F (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: The percentage proportion of older people in Indonesia is increasing, indicating that Indonesia is a country with a population structure leaning towards the elderly. If one does not die before that, every human being will surely experience an aging process that can cause various problems such as health problems. Anxiety is one of the serious health problems in the elderly. Physical exercise, such as yoga, can help reduce anxiety level. Aim: To analyze correlation between yoga exercise and level of anxiety in the elderly in Posyandu Lansia Yuswo Widodo Surabaya. Method: This research used a pre-experimental study with pre-posttest one group design, held on the 26th of July 2019 until the 16th of September 2019. The samples in this study were 22 people, all of whom were elderlies who routinely visited and have participated in 16x yoga exercise for two months. The research instrument this study used was HARS. Kendall’s Tau B was used for the data analysis. Results: data analysis shows that there was a correlation between routine yoga exercise and the level of anxiety in the elderly in Posyandu Lansia Yuswo Widodo Surabaya p=0,030. Pretest results showed that there were 14 elderly with mild anxiety and eight elderly with moderate anxiety. post-test data showed five elderly with mild anxiety levels and 17 people who did not have anxiety. Conclusion: There was a correlation between the routine of yoga exercise and the level of anxiety in the elderly in Posyandu Lansia Yuswo Widodo Surabaya.